By implication. Didactical strategy in Psalm 1 - Lombaard, Christo J. S. (Old Testament Essays, 1999)
The paper inverstigates the didatic strategy of Psalm 1. It elicits the effect of juxtaposing positive and negative statements in the psalm and the way in which it infuses in the reader or hearer a striving to choose the right way of living rather than compelling such a choice
free
Keywords: Ecclesiastes; Psalm 1; Yahweh; job